Creating Creative Technologists: playing with(in) education - Walker, C; Connor, AM; Marks, S (Springer, 2015)
Since the industrial revolution, the organization of knowledge into distinct scientific, technical or creative categories has resulted in educational systems designed to produce and validate particular occupations. The methods by which students are exposed to different kinds of knowledge are critical in creating and reproducing individual, professional or cultural identities. (“I am an Engineer. You are an Artist”). The emergence of more open, creative and socialised technologies generates challenges for discipline-based education. At the same time, the term “Creative Technologies” also suggests a new occupational category (“I am a Creative Technologist”). This chapter presents a case-study of an evolving ‘anti-disciplinary’ project-based degree that challenges traditional degree structures to stimulate new forms of connective, imaginative and explorative learning, and to equip students to respond to a changing world. Learning is conceived as an emergent process; self-managed by students through critique and open peer review. We focus on ‘playfulness’ as a methodology for achieving multi-modal learning across the boundaries of art, design, computer science, engineering, games and entrepreneurship. In this new cultural moment, playfulness also re-frames the institutional identities of teacher and learner in response to new expectations for learning.